2017
DOI: 10.21475/ajcs.17.11.06.p175
|View full text |Cite
|
Sign up to set email alerts
|

Temperature management of potatoes in packaging with reusable plastic crates in the fresh produce supply chain

Abstract: Although initially the introduction of reusable plastic crates was because off cost savings, their speed of adoption was accelerated by environmental considerations. RPCs having a lower direct impact across a broad range of environmental parameters when compared with than display-ready containers (DRCs)., Also RPCs can have an indirect effect with lower levels of produce waste, further reducing the environment impact of using plastic crates. This paper considers the temperature management challenges with packa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…These studies showed that effective design of ventilating packaging for horticultural produce required careful consideration of a conflicting objectives: (a) to reduce 7/8 pre‐cooling time setting a certain opening in the pre‐cooling box, and (b) ensuring mechanical integrity of the box and resistance to impact and compressive loads. Therefore, in the actual production process, the application of plastic pre‐cooled packaging is wider than before (Jones, Bishop, Porter, & Saowapa, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…These studies showed that effective design of ventilating packaging for horticultural produce required careful consideration of a conflicting objectives: (a) to reduce 7/8 pre‐cooling time setting a certain opening in the pre‐cooling box, and (b) ensuring mechanical integrity of the box and resistance to impact and compressive loads. Therefore, in the actual production process, the application of plastic pre‐cooled packaging is wider than before (Jones, Bishop, Porter, & Saowapa, 2017).…”
Section: Methodsmentioning
confidence: 99%